HUBUNGAN KARAKTERISTIK DAN PENGETAHUAN IBU DENGAN KEMANDIRIAN TOILET TRAINING ANAK TODDLER - tuti asrianti utami; Mismadonaria Mismadonaria; Anna Rejeki Simbolon (Poltekkes Kemenkes Jambi, 2020)
Background: Toilet training is the most important part of the development of toddlers (1-3 years), in the process of urinating and defecating. Toilet training can be carried out well, of course, it requires the participation of parents, especially mothers. Mother's knowledge is needed to enable her child to do proper toilet training. This study aims to determine the relationship between characteristics and knowledge of respondents with the independence of toilet training for toddlers in Tanah Tinggi, Jakarta. Method: This quantitative research with a correlative descriptive design with a cross-sectional approach. Total sampling used in sampling many 86 respondents. The analysis tool uses u ji chi-square (AAP, 2020). Results: The results showed that most respondents had good knowledge and good behaviour in the independence of toddler toilet training (41.8%), the age of respondents was 26-35 years as many as 32 (48.5%), the education level of the respondents was mostly educated Medium as many as 25 respondents (29.1%), the respondent's occupation is as a housewife as many as 44 respondents (54.3%). The results obtained were there was no relationship between age (0.091> 0.05), education (0.458> 0.05), work (0.333> 0.05) and knowledge (0.083> 0.05) of respondents with toddler toilet training independence. Conclusion: Based on the results of the study, it is recommended that health workers and cadres should provide health promotion about the importance of bathing the right toilet training by paying attention to the readiness of toddlers.